HUBUNGAN PENGETAHUAN DENGAN MINAT IBU BALITA TENTANG TAMAN POSYANDU DI KELURAHAN COKROMENGGALAN KECAMATAN PONOROGO KABUPATEN PONOROGO - Sumini Sumini; Arifatul Rosidah (Jurnal Delima Harapan, 2018)
Taman Posyandu is development of posyandu purnama or independent which give additional service to develop early childhood and bina keluarga balita. Total data of toddler in posyandu pos 3 Cokromenggalan Village has 52 people. At 2016, in posyandu pos 3 Cokromenggalan Village has 22 toddler that followed Taman Posyandu. Based on study of preliminary studies there are 6 from 10 mother of toddler is lack of knowledge about Taman Posyandu. The purpose of research is to know The connection knowledge mother of toddler with interest to the mother of toddler about Taman Posyandu in posyandu pos 3 Cokromenggalan, Cokromenggalan Village, Ponorogo District, Ponorogo Regency. This type of research is quantitative. The research design used Cross Sectional and this research was conducted at Posyandu Pos 3 Cokromenggalan in January 2017. The population is all the mothers of toddler with the number of 52, the number of samples 30, with the technique of Accidental Sampling. Independent variables (knowledge) and dependent variables (interests). Instrument with questionnaire, and Spearman Rank statistical test at 0.05 significance level. Based on research result of knowledge about taman posyandu half of 15 respondents (50%) with less knowledge. Interest in following the taman posyandu almost half of 16 respondents (53.3%) with negative interest. The result of statistic test by using Spearman Rank shows that ρ = 0,000 with correlation coefficient value 0.803, ρ which can be <0.05 so that H0 is rejected which means there is the correlations knowledge of mother toddler with interest to the mother of toddler about taman posyandu in posyandu post 3 Cokromenggalan,Cokromenggalan village, Ponorogo district, Ponorogo regency with a level flatness is very strong. The conclusion is that mother have low knowledge about Taman Posyandu can cause the interest mother about Taman Posyandu is low. It is recommended that local health personnel to improve the extension of the importance of the visit to the Taman Posyandu to toddler and useful for enhance mother of knowledge about the importance of monitoring, detecting growth for children, providing health services and stimulation of education early.